Uji Validitas dengan Aiken’s V Terhadap Multimedia Interaktif Berbasis Digital Pada Mata Pelajaran PJOK di SMP - Qaulan Tsaqila; Murlia Irmayanti; Nurhikmah H; Suryadi Ishak; Safaruddin (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2026)
The development of 21st-century technology has encouraged the use of digital media as a more innovative and interactive learning tool, including in PJOK instruction. The topic of healthy, nutritious, and balanced eating patterns is often perceived as abstract by students due to the limited availability of engaging visual media. This study aims to examine the validity of a digital-based interactive multimedia using Aiken’s V formula as a learning medium for PJOK in junior high schools. This research employed an R&D design using the ADDIE approach, consisting of the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by media experts and material experts using a structured assessment instrument. The results indicate that the developed interactive multimedia can be easily operated by students and supports improved understanding of the material. The media expert validation for 20 assessment items produced an Aiken’s V coefficient of 0.87, while the material expert validation for 14 items produced a coefficient of 0.82. Both results fall into the “very valid” category, indicating that the media meets standards of content feasibility, visual quality, language clarity, and usability. Therefore, the digital-based interactive multimedia is declared highly suitable for use in PJOK learning, as it enhances learning effectiveness and provides a more engaging and meaningful learning experience for students